Bilateral retrorenal colon-a case report - Khaladkar, Sanjay M.; Tomar, Shantanu Singh; Alawadhi, Akshay; Sehrawat, Vipul (International Journal of Research in Medical Sciences, 2017)
Ascending and descending colon normally lie in anterior pararenal space anterior to kidneys. Extension of colon behind kidney is rare. It is more frequently found on the left side behind lower pole of the left kidney. Bilateral retrorenal colon is rare. Its detection is important prior to Retrorenal, Percutaneous nephrolithotomy (PCNL) to avoid complications. We report a case of bilateral retrorenal colon detected incidentally in a case of obstructive jaundice.